(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This literature review provides an in-depth analysis of the pathogenic significance of the atherogenic index of plasma (AIP) in predicting the onset and progression of diabetic retinopathy (DR) in patients with diabetes mellitus. The paper systematically highlights the mechanisms of lipidotoxicity, accumulation of small dense LDL (sdLDL) particles, oxidative stress, and retinal microvascular damage in light of major international clinical trials such as FIELD, ACCORD Eye, and LENS. Special emphasis is placed on evaluating the diagnostic specificities of the AIP index considering regional dietary patterns and the high prevalence of metabolic syndrome within the Uzbek population.